Fenomena Islamophobia Di Korea Selatan Pada Tahun 2016-2024 - Ramadhanty, Zahwa Fabilla; Hasbi Aswar (Institut Muslim Cendekia, 2025)
South Korea is promoted as a Muslim-friendly tourist destination, with an increasing Muslim population, as well as government initiatives in providing facilities that support Muslim needs, but discrimination against the Muslim community still occurs in the country. This research will discuss the phenomenon of Islamophobia in South Korea using the concept of Islamophobia from The Runnymede Trust which identifies four main indicators of Islamophobic practices: discrimination, exclusion, violence, and prejudice. The research method used is a qualitative research method by collecting online documents including journals, websites, social media and films relevant to this research and analyzing them with a content analysis approach to find forms of Islamophobia in South Korea. The research shows that the Muslim community experiences difficulties in accessing employment, public services, and faces negative stereotypes reinforced by the media. Cases of hate speech, refusal to build mosques, and barriers to worship reflect the deep-rooted Islamophobia in South Korean society. This research provides insight into the contradiction between the government's campaign and the social reality faced by the Muslim community in South Korea, and analyzes the factors that influence Islamophobic sentiments.